PENGARUH LOCUS OF CONTROL, GAYA KEPEMIMPINAN, DAN KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR (STUDI KASUS DI BPKP PERWAKILAN SUMATERA UTARA) - Natasia Andini; Triani Sylvana Sihombing; Ema Saputri Br Tarigan; Tetty Tiurma Uli Sipahutar (Yayasan Akrab Pekanbaru, 2019)
Abstract The accounting profession has an important role in the provision of reliable financial information for thr government, investors, creditors, shareholders, employees, debtors, also for the community and other parties concerned. The performance of auditorsis the ability of an auditor to produce findings or results of the examination of inspection activities for the management and financial responsibilities are carried out in an inspection team. Factor affecting the performance of the auditor is locus of control, leadership style and organizational commitment. The purpose of this study was to determine the effect of locus of control, leadership style and organizational commitment on the performance of auditors at BPKP of North Sumatra Representation Office. Research tool used was a data analysis technique multiple linear regression, F- test, t test. The location study performed at BPKP, which in the North Sumatra Respresentation Office. Based on the results of analysis show that the locus of control, leadership style and organizational commitment have positive influence on the performance of auditors at BPKP of North Sumatra Representation Office.